Homogenizing Schedule Performance Index (SPI) in Construction Projects - Fazeli Moslehabadi, Ali (International journal of industrial engineering and operational research, 2020)
Schedule Performance Index (SPI) is one of the Earned Value Method indicators for assessing a project performance schedule. The problem with this index while actual implementation of project for measuring a project scheduling performance is that the denominator and numerator are not homogeneous. In other words, the numerator is made of volume and the denominator made of time. Therefore, the SPI index does not provide project managers with precise guidelines for indicating a project's actual performance in terms of time and project implementation. Therefore, it is necessary to obtain a practical method for homogenizing the numerator and denominator of this indicator that not only provides a precise criterion for a project schedule performance but also proper guidelines to make on-time and correct decisions by project managers and owners. This paper aims to present a method for this purpose by giving an example of unit price contract in the supposed underground hydro power plant project.